The Influence of Small Biomolecules, Salts and Buffers on the Molecular Recognition of Amide Naphthotube in Aqueous Solutions. Issue 2 (17th November 2022) - Li, Ming‐Shuang; Dong, Yi‐Wei; Pang, Xin‐Yu; Chai, Hongxin; Wang, Xiaoping; Jiang, Wei
Abstract: We found the binding affinities of amide naphthotube to neutral organic molecules in water are not influenced by most of small biomolecules, inorganic salts, and PBS and Tris buffers but are reduced in HEPES buffer through competitive binding. Nevertheless, salts do change the binding affinities of amide naphthotube to charged molecules through a screening effect. Abstract : The binding affinities of amide naphthotube to neutral organic molecules in water are not influenced by a majority of small biomolecules, inorganic salts, and PBS and Tris buffers.